PLAN ESTRATÉGICO DE MARKETING PARA FOMENTAR LOS ATRACTIVOS TURÍSTICOS DE LA PARROQUIA CAMARONES, CANTÓN ESMERALDAS, PROVINCIA DE ESMERALDAS, AÑO 2022. - Rezabala Barrezueta, Maryuri Nathalya (2022)
The purpose of this research is to develop a strategic plan for the promotion of the tourist resources of the Camarones parish, in addition, to know about the tourist needs that this place is suffering due to the lack of interest of the authorities, and this causes that the tourist activity is tiny making the economy of the place low. Tourism is currently a fundamental axis for economic development, which is why in constant situations investment budgets are being offered with the aim of promoting and promoting tourism. The general objective of this study is to demonstrate a strategic marketing plan to promote tourist attractions in the Camarones parish, Canton Esmeraldas, for which several methods were used to result in this research, such as investigative, analytical and techniques such as observation. and surveys; By using the survey method, I obtained much more accurate and true information from the people or tourists who have visited that place.